Proinflammatory circulating markers: new players for evaluating asymptomatic acute cardiovascular toxicity in breast cancer treatment. (9th January 2021) - Micheletti, P. L.; Carla-da-Silva, J.; Scandolara, T. B.; Kern, R.; Alves, V. D.; Malanowski, J.; Victorino, V. J.; Herrera, A. C. S. A.; Rech, D.; Souza, J. A. O.; Simão, A. N. C.; Panis, C.; et al.
Abstract : Purpose: This study aimed to evaluate markers of cardiac damage (total CK, CKMB and CRP), inflammatory markers (free iron, homocysteine and TNF-α) as well as lipidogram in breast cancer patients undergoing acute cycles of doxorubicin (DOX), paclitaxel (PTX) or trastuzumab (TZ) and to verify if there is an association between these markers and the toxicity of the chemotherapeutic treatment. Methods: Included in the study were 120 breast cancer patients and 50 healthy controls. All analyzes were performed on automated systems. For the statistical analysis, each group was compared with the controls according to their normality by Student's t-test and Mann-Whitney test. Results: Our results showed that DOX treatment led to increased hsCRP (4.80 ± 1.23 mg/dL, p = 0.0005), triglycerides (187.6 ± 25.06, p = 0.0231), TNF-α (42.31 ± 17.96 pg/mL, p = 0.01) and Fe levels (138.8 ± 18.6 μg/dL, p = 0.0193). In the meantime, PTX induced changes in CK-MB (8.78 ± 4.2 U/L, p = 0.0361), hsCRP (7.12 ± 1.87 mg/dL, p = 0.0006), cholesterol (201.7 ± 19.54, p = 0.05), triglycerides (201.7 ± 19.54, p = 0.0277), TNF-α (38.27 ± 9.12 pg/mL, p = 0.023), homocysteine (10.95 ± 0, 86 μmol/L, p = 0.005), and free iron (113 ± 18 6 μg/dL, p = 0.045) while TZ augmented CK-MB (6.9 ± 1.97 U/L, p < 0.00), hsPCR (3.12 ± 0.68 mg/dL, p = 0.095), cholesterol (218.3 ± 16.79, p = 0.0317), triglycerides (218.3 ± 16.79, p = 0.0127), TNF-α (89.6 ± 12.11, p = 0.032), homocysteine (9.95 ± 1.15 μmol/L, p = 0.0396), free iron (120.5 ± 4.64 μg/dl, p = 0.0058) as well. Conclusions: Our data demonstrated the existence of a proinflammatory net triggered by breast cancer chemotherapy that could increase cardiomyocytes permeability and allow the leakage of circulating proteins as CK-MB and induce the production of hsCRP.